Concepts of poverty and social exclusion in Europe. (November 2015) - Madanipour, Ali; Shucksmith, Mark; Talbot, Hilary
This paper provides a critical analysis of the concepts of poverty and social exclusion in three parts. First, it examines the relationship between poverty and social exclusion, a distinction that has been the subject of analysis, debate and controversy. Second, the concepts of poverty and social exclusion as used in the European policy discourse are analysed, and how changes in terminology, links to the economic growth agenda, and emphasis on employment as a response can be noticed. The recognition of the 'territorial dimension' of poverty and social exclusion has been an increasingly important feature of EU discourse and actions. Third, the paper explores the inherent territoriality of poverty and social exclusion, which has paved the way for localised spatial responses. The authors argue that economic concerns have triggered a continuous tendency to narrow down the focus of definition and action, in order to offer clarity of scope to researchers and policy makers, but that such narrowing could also undermine our ability to address a complex multi-dimensional process. In particular, prioritising economic dimensions to the neglect of the other aspects of social exclusion is problematic in dealing with major social problems.